ANCHOR: Navigation, Routing and Collision Warning during Operations in Harbors*. Issue 23 (2016) - Trzuskowsky, Andreas; Hoelper, Carsten; Abel, Dirk
Abstract: The traffic density in and around harbors is rising continuously and it is challenging to maneuver a ship through the port to or from its assigned mooring dock. Thus, the ANCHOR project aims at assisting pilots and port operators during piloting large vessels safe and economically in time within harbor areas. This work focuses on the highly accurate, portable, and reliable navigation system developed within the project ANCHOR. The system suggests routes and has a built-in collision warning system to enhance safety. To be able to provide the mentioned functionality portabledevices are handed out to the pilots. The devices can be used ship independent and therefore shipowners do not need to equip their vessels with extra technology. The navigation units measure ship position, and attitude. Furthermore, they are connected to a server via a communication link to share their information, and measurements. The server additional receives environmental data like wind, and current from the projects sensor network as well as AIS data from an integrated AIS receiver. Combining all the data, the server delivers optimized routing information, and collision warnings to the pilots. Achieved results showing the potential of the system as well as further planned tests and demonstrations are introduced in this paper.